Status and prospects of using aviation biofuels - Ivantsov, Mikhailo; Beyder, Elynor Yenia; Baranovskyy, Mikhaylo (Problems of Environmental Biotechnology, 2024)
The current state and prospects for the use of aviation biofuels are considered